Rescate de la identidad cultural de Chacras - Robalino Farías, Mishell Eloísa (Machala : Universidad Técnica de Machala, 2018)
The aim is to approach from the pictorial and representative appreciation the symbolic step of the Bolivarian heroine named Manuela Sáenz who in some way wishes to rescue the cultural identity of the Chacras parish belonging to Cantón Arenillas thanks to the historical research and oral information of its inhabitants. We have made an appropriation of emblematic equestrian pictorial works to be able to adapt it to our proposal of equestrian painting of the heroine Manuelita Sáenz, in the acrylic technique, that is to say, an equestrian portrait. The historical memory of this town, added to the collective imaginary represents a cycle of the culture of this territory. Also a form of the imaginary is recovered in a material identification, as well as evidence the archetype of the character as was the heroine Manuelita Sáenz. According to Edgar Morin Develops the concept of collective Imaginary: it is the set of myths, forms, symbols, types, motives or figures that exist in a society at a given moment, so this research work of scientific humility tries to rescue it through of pictorial art. In the first chapter that deals with the conceptualization of the artistic object.The research work is directed to the cultural identity that Manuela Sáenz left in her current parish, chacras; Through the investigation it is intended to address, how this Bolivarian heroine named Manuela Sáenz granted an important legacy to the inhabitants of said parish.
Se pretende abordar desde la apreciación pictórica y representativa el paso simbólico de la heroína bolivariana llamada Manuela Sáenz que de alguna manera desea rescatar la identidad cultural a la parroquia Chacras perteneciente al Cantón Arenillas gracias a la investigación histórica y de información oral de sus habitantes. Hemos realizado un apropiacionismo de obras pictóricas ecuestres emblemáticas para poder adaptarla a nuestra propuesta de pintura ecuestre de la heroína Manuelita Sáenz, en la técnica acrílica, es decir un retrato ecuestre. La memoria histórica de este pueblo, sumado al imaginario colectivo representa un ciclo de la cultura de este territorio. Asimismo una forma del imaginario es recuperada en una identificación material, así como evidenciar el arquetipo del personaje como fue la heroína Manuelita Sáenz. Según Edgar Morin Desarrolla el concepto de Imaginario colectivo: es el conjunto de mitos, formas, símbolos, tipos, motivos o figuras que existen en una sociedad en un momento dado, por lo que este trabajo de investigación dese la humildad científica intenta rescatarlo a través del arte pictórico. En el primer capítulo que trata sobre la conceptualización del objeto artístico. El trabajo de investigación se encuentra direccionado a la identidad cultural que dejo a su paso Manuela Sáenz en la actual parroquia chacras; mediante la investigación se pretende abordar, como esta heroína bolivariana llamada Manuela Sáenz otorgo un legado importante a los habitantes de dicha parroquia.
Keywords: CULTURA; ARTE PICTORICO; MEMORIA HISTORICA; PINTURA ECUESTRE